2019
DOI: 10.3390/met9020193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bubbles on Crystallization Behavior of CaO–SiO2 Based Slags

Abstract: Surface longitudinal cracks are a serious problem and particularly prevalent in the casting of peritectic steel (carbon content between 0.10%C and 0.18%C, non-alloyed). It is usually alleviated by controlling the horizontal heat transfer from the steel shell to the mold through increasing the crystallization performance of slags. In the actual continuous casting process, a large number of bubbles are formed in the molten slags, and the crystallization properties of the mold fluxes are affected by bubbles. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The activation energies of crystallization were determined by the Freeman-Carroll method [20][21][22][23]. The Freeman-Carroll method is one of the most commonly methods to analyze the crystallization kinetics based on DSC/DTA experiments.…”
Section: Activation Energy Of Crystallizationmentioning
confidence: 99%
“…The activation energies of crystallization were determined by the Freeman-Carroll method [20][21][22][23]. The Freeman-Carroll method is one of the most commonly methods to analyze the crystallization kinetics based on DSC/DTA experiments.…”
Section: Activation Energy Of Crystallizationmentioning
confidence: 99%
“…Li et al observed that by stirring the molten mold flux, the crystallization temperature could be increased, and the crystallization fraction of the stirred mold flux at the initial stage of crystallization was significantly higher than that of the static one. In addition, the addition of carbonate materials, such as CaCO 3 , Na 2 CO 3 , and Li 2 CO 3 , into mold fluxes can produce bubbles, and the bubble formation also influences the crystallization behavior of the mold fluxes . The effects of different methods and factors on the crystallization of mold fluxes have been explored, but it is difficult to achieve real‐time regulation of the crystallinity of mold fluxes.…”
Section: Introductionmentioning
confidence: 99%